Availability of environmental resources vs. health conditions and wellbeing of residents 60+ of rural areas - Błachnio, Aleksandra; Maliszewski, Wojciech; Molesztak, Aldona (Journal of Education, Health and Sport, 2017)
Admission. The number of Polish old increases regularly. At the same time, the debate on how improving the quality of life of the old has been renewed, but the scientists need to study if the “successful ageing” can be obtained by an average senior. Aim of the study. The goal of this research was to measure health and well-being of residents 60+ living in villages and to investigate to what extent the environmental resources meet their needs. Material and methods. Satisfaction with Life Scale (Diener at al., 1985) and a structured interview assessing the quality of health conditions and environmental resources were carried out in 2016 on a sample of 120 seniors. Each participant gave consent for participation in the study. The Statistica 12.5 software was use for analyses. Results. The overall measure of satisfaction with life of the respondents (M=18,83 SD=5.45) is moderate. Seniors who declare stronger sense of diseases have lower well-being than seniors with better subjective assessment of health (Tukey HSD=27,84, p=0,01). Multimorbidity and polypharmacy are present to a limited extent. The issue of unmet needs of elderly individuals in villages affected more than half of the respondents. Older residents of rural areas have but limited environmental resources. Conclusions. Robert Havighurst’s model of “successful ageing” and the right for “the greatest good for the greatest number” in Poland are merely theoretical constructs. The burden of caregiving on the ageing population is still mostly on their families. Seniors lack satisfactory environmental resources and state care.